Undivided rights: Women of color organizing for reproductive justice - Silliman, Jael; Fried, Marlene Gerber; Ross, Loretta; Gutiérrez, Elena (Haymarket Books, 2016)
Undivided Rights captures the evolving and largely unknown activist history of women of color organizing for reproductive justice—on their own behalf.Undivided Rights presents a textured understanding of the reproductive rights movement by placing the experiences, priorities, and activism of women of color in the foreground. Using historical research, original organizational case studies, and personal interviews, the authors illuminate how women of color have led the fight to control their own bodies and reproductive destinies. Undivided Rights shows how women of color—-starting within their own Latina, African American, Native American, and Asian American communities—have resisted coercion of their reproductive abilities. Projected against the backdrop of the mainstream pro-choice movement and radical right agendas, these dynamic case studies feature the groundbreaking work being done by health and reproductive rights organizations led by women-of-color.The book details how and why these women have defined and implemented expansive reproductive health agendas that reject legalistic remedies and seek instead to address the wider needs of their communities. It stresses the urgency for innovative strategies that push beyond the traditional base and goals of the mainstream pro-choice movement—strategies that are broadly inclusive while being specific, strategies that speak to all women by speaking to each woman. While the authors raise tough questions about inclusion, identity politics, and the future of women’s organizing, they also offer a way out of the limiting focus on "choice."Undivided Rights articulates a holistic vision for reproductive freedom. It refuses to allow our human rights to be divvied up and parceled out into isolated boxes that people are then forced to pick and choose among.
Keywords: afro-féminisme; amériques; approches et analyses; discours dominant; droits des femmes*; histoire et politique; intersectionnalité; inégalités; justice reproductive; militance; régions géographiques; sofia; système colonial; systèmes d'oppressions; thématiques; états-unis

« Gender Equality and Economic Inequality: Impact on Marriage » dans Gender and couple relationships - Coontz, Stephanie (Gender and couple relationships, 2016)
Changes in aggregate marriage rates and in the internal dynamics of individual marriages should be understood as the outcome of two powerful but very different trends in gender and class relations. One trend is the uneven but undeniably dramatic progress toward equality in personal life and cultural values, which has led to widespread repudiation of centuries-old gender hierarchies. The other trend is an equally powerful movement toward growing inequality, insecurity, and unpredictability in economic life, which has resulted in substantial losses for the most historically vulnerable and least-educated sections of the workforce. The ongoing gender revolution interacts with widening economic inequality in complex ways, increasing the benefits of marriage for individuals with higher earning power while increasing the risks of marriage for low-income individuals, especially women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; care; cours; discipline; discours dominant; droits des femmes*; famille; inégalités; mariage; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; soc2262; sociologie; systèmes d'oppressions; thématiques; états-unis

Kimberlé Crenshaw: The urgency of intersectionality | TED Talk - Crenshaw, Kimberlé (TedTalk, 2016)
Now more than ever, it's important to look boldly at the reality of race and gender bias -- and understand how the two can combine to create even more harm. Kimberlé Crenshaw uses the term "intersectionality" to describe this phenomenon; as she says, if you're standing in the path of multiple forms of exclusion, you're likely to get hit by both. In this moving talk, she calls on us to bear witness to this reality and speak up for victims of prejudice.
Keywords: activisme; afro-féminisme; approches et analyses; com5170; cours; discipline; droit; droits civiques; droits des femmes*; droits humains; féminisme afroaméricain; histoire et politique; intersectionnalité; justice sociale; militance; premier cycle; science politique et droit; thématiques

A gendered human rights analysis of Ebola and Zika: Locating gender in global health emergencies - Davies, Sara E.; Bennett, Belinda (International Affairs, 2016)
Globally gender remains a key factor in differing health outcomes for men and women. This article analyses the particular relevance of gender for debates about global health and the role for international human rights law in supporting improved health outcomes during public health emergencies. Looking specifically at the recent Ebola and Zika outbreaks, what we find particularly troubling in both cases is the paucity of engagement with human rights language and the diverse backgrounds of women in these locations of crisis, when women-specific advice was being issued. We find the lessons that should have been learnt from the Ebola experience have not been applied in the Zika outbreak and there remains a disconnect between the international public health advice being issued and the experience of pervasive structural gender inequalities among those experiencing the crises. In both cases we find that responses at the outbreak of the crisis presume that women have economic, social or regulatory options to exercise the autonomy contained in international advice. The problem in the case of both Ebola and Zika has been that leaving structural gender inequalities out of the crisis response has further compounded those inequalities. The article argues for a contextual human rights analysis that takes into account gender as a social and economic determinant of health.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; amérique latine; amériques; approches et analyses; care; droits des femmes*; inégalités; périodes historiques; ressource en ligne; régions géographiques; santé; santé publique; systèmes d'oppressions; thématiques

Un projet pour penser, dire et transformer les rapports sociaux de sexe : les études féministes au Québec - Descarries, Francine (Les femmes dans le monde académique : perspectives comparatives, 2016)
Keywords: amériques; approches et analyses; droits des femmes*; pédagogie; québec; rapports sociaux de sexe; régions géographiques; thématiques; université

Égalité entre les femmes et les hommes. Six niveaux pour comprendre et agir - Drion, Claudine (En question, 2016)
Le Monde selon les femmes, ONG belge de développement et Centre international de formation en genre, propose depuis plus de vingt ans des formations et des recherches-actions sur l’égalité entre les femmes et les hommes avec des associations partenaires du Sud.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; belgique; cours; discipline; droits des femmes*; europe; histoire et politique; inégalités; justice sociale; outils; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; sex2283; sofia; systèmes d'oppressions; thématiques; travail social; trs1205

The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Agir sans "nous" - Lamoureux, Diane (Les possibles du féminisme : agir sans "nous", 2016)
«Les féminismes expriment fondamentalement une révolte. Savoir ce que l'on refuse, ce qui ne peut plus durer, ce qui constitue une injustice ne suffit pas pour établir ce que l'on recherche ni même pour trouver les moyens d'y parvenir. Et puisque les motifs de révolte sont nombreux et procèdent de l'expérience singulière de chacune, "faire mouvement" pose problème.» Afin d'établir sa légitimité, le féminisme a d'abord postulé que toutes les femmes sont liées par une oppression commune. Si le constat reste exact, l'universalisme féminin mène à une impasse. Ne faudrait-il pas plutôt construire des solidarités qui n'obligent pas certaines à sacrifier leurs enjeux sur l'autel de l'unité? Néolibéralisme, liberté, justice sociale, défense des droits ou rapport à l'État, les réflexions courageuses de Diane Lamoureux abordent de front les questions qui animent le féminisme des dernières décennies et qui traversent la pensée politique au Québec. En cherchant à cerner les conditions de radicalité du féminisme, elle rompt une fois de plus avec la tentation du conformisme. L'unisson n'est ni possible ni souhaitable. Le féminisme ne fait pas mouvement: il est mouvement. -- 4e de couv.
Keywords: EDI; amériques; approches et analyses; cours; droits des femmes*; fem1000; histoire et politique; justice sociale; mouvements sociaux; patriarcat; premier cycle; québec; régions géographiques; sexisme; systèmes d'oppressions; thématiques

À la rencontre des femmes Autochtones du Québec - Larivière, Widia; Boulanger, Sébastien; Champagne, Julie; Dubois, Christian; Bouchard, Sylvie; Québec (Province). Conseil du statut de la femme (Conseil du statut de la femme, 2016)
L’organisme Femmes Autochtones du Québec et le Conseil du statut de la femme ont uni leur expertise pour mettre en lumière la réalité des femmes autochtones du Québec. Les femmes autochtones et les femmes non autochtones ont une histoire qui leur est propre, des origines différentes et une identité distincte, ce qui ne les empêche pas de nouer des partenariats1 et de nourrir des aspirations communes. Comme par exemple valoriser la parole et l’action des femmes, souhaiter l’autodétermination et la nondiscrimination pour toutes.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; care; cours; droits des femmes*; féminisme autochtone; histoire et politique; justice reproductive; pol4105; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; travail; violences; éducation

Sexualized Violence and Colonialism: Reflections on the Inquiry into Missing and Murdered Indigenous Women - Razack, Sherene (Canadian Journal of Women and the Law, 2016)
Introduction to the special isuue of the Canadian Journal of Women and the Law on the "Missing and Murdered Indigenous Women Conference".
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; féminicide; intersectionnalité; justice sociale; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Défense des droits des femmes : extraits - Wollstonecraft, Mary (Folio 2 euros, 2016)
"J'espère que, quand on reverra la Constitution, les droits de la femme seront enfin comptés pour quelque chose et respectés comme ils doivent l'être, surtout quand il sera bien prouvé, comme cela ne peut manquer de l'être, que la raison exige que l'on fasse attention à leurs plaintes et réclame hautement justice pour une moitié de l'espèce."--Page 4 de la couverture.
Keywords: 1700-1799; citoyenneté; cours; droits des femmes*; europe; fem1000; histoire et politique; incontournable; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques

Épitre dédictoire - Wollstonecraft, Mary (Défense des droits des femmes: extraits, 2016)
Keywords: 1700-1799; citoyenneté; cours; droits des femmes*; europe; fem1000; histoire et politique; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques